Trust as a mediating factor linking online customer reviews and brand awareness to purchase intention on Shopee in Solo - Hisan, Rumaisa; Saputro, Edy Purwo (Institute of Computer Science (IOCS), 2025)
The rapid expansion of e-commerce in Indonesia has made online reviews and brand cues important sources of information for consumers. This study examines how online reviews and brand awareness can influence the purchase intention of Shopee users in Solo, with trust assessed as a mediating variable. Using data from 100 respondents analyzed through the PLS-SEM method, the results show that online review ( and brand awareness (significantly increase purchase intention, supported by a strong R-square value of 0.779, which indicates that this research model has strong predictive power. However, trust () does not significantly affect purchase intention and does not mediate the relationship between the independent variables and purchase intention. Theoretically, this study contributes to the understanding of digital consumer behavior by showing the limited mediating role of trust in established e-commerce platforms. Practically, the findings indicate that improving review quality and strengthening brand identity can be more effective strategies than relying on trust building alone.